Instalación y manejo de redes (LAN) en plataforma UNIX, Módulo III - DECDFI (My University, 1860)
In open Desktop, you can control your computer by clicking on or dragging icons and by selecting actions from menus. Such graphical environments (also called graphical user interfaces or GUls) were not widely used until computers with the required and speed became generable available.
Keywords: UNIX; red; administración; ambiente; conectividad